Mixed CAD Method to Develop Gear Surfaces Using the Relative Cutting Movements and NURBS Surfaces. (2015) - Tolvaly-Roşca, Ferenc; Forgó, Zoltán
Abstract: The paper proposes a pure CAD modeling solution to universally generate surfaces and solid models of gears, which are intended to be used in contact and FEA studies in virtual environment. The developed method uses the known NURBS surfaces modeling methods, combined with the input in CAD environment of the relative cutting motions between tool and gear. The cutting motions are also divided in relative motion steps, the cutting tool profiles are reduced to discreet points, fixed in 3dpolyline vertexes, and theirs coordinates are read and stored after each moving steps. The obtained points contain discreet points from the generated surfaces. Using this points, and usual NURBS modeling methods, the generated surfaces are built. In final stage, this method should be a much faster alternative to the very slow, and huge calculating power consuming, solid modeling with Boolean operations.